γ-H2AX Kinetics as a Novel Approach to High Content Screening for Small Molecule Radiosensitizers - Fu, Shibo; Yang, Ying; Tirtha, Das; Yen, Yun; Zhou, Bing-sen; Zhou, Ming-Ming; Ohlmeyer, Michael; Ko, Eric C.; Cagan, Ross; Rosenstein, Barry S.; Chen, Shu-hsia; Kao, Johnny (PLOS ONE, 2012)
Background Persistence of γ-H2AX after ionizing radiation (IR) or drug therapy is a robust reporter of unrepaired DNA double strand breaks in treated cells. Methods DU-145 prostate cancer cells were treated with a chemical library ±IR and assayed for persistence of γ-H2AX using an automated 96-well immunocytochemistry assay at 4 hours after treatment. Hits that resulted in persistence of γ-H2AX foci were tested for effects on cell survival. The molecular targets of hits were validated by molecular, genetic and biochemical assays and in vivo activity was tested in a validated Drosophila cancer model. Results We identified 2 compounds, MS0019266 and MS0017509, which markedly increased persistence of γ-H2AX, apoptosis and radiosensitization in DU-145 cells. Chemical evaluation demonstrated that both compounds exhibited structurally similar and biochemical assays confirmed that these compounds inhibit ribonucleotide reductase. DNA microarray analysis and immunoblotting demonstrates that MS0019266 significantly decreased polo-like kinase 1 gene and protein expression. MS0019266 demonstrated in vivo antitumor activity without significant whole organism toxicity. Conclusions MS0019266 and MS0017509 are promising compounds that may be candidates for further development as radiosensitizing compounds as inhibitors of ribonucleotide reductase.